Determination of optimal location of circuit board and battery on 3D glasses by considering nose load and subjective discomfort - Chang, J. (2013)
The current shutter type (SG) 3D glasses in the market are heavy (41 g) and have a poor weight balance due to a battery and a circuit board on the temples of the glasses. Therefore, it causes high pressure on the nose and discomfort for the users. This study determined the optimal location of a circuit board and a battery for SG type 3D glasses. Four 3D glasses with different weight distributions (the battery and the circuit board locations: front, middle, ear, and rear positions) were employed in the experiments. Subjective discomfort ratings (100 point scale) around the nose and the posterior edge of the ear were obtained after wearing the four 3D glasses. Also, at the same time the load on the nose was measured by using FSR (force sensing resistor) film sensors. As a result, the front position showed the highest subjective discomfort rating on the nose. Discomfort ratings on the nose were decreased significantly as the location of the battery and circuit board moved backward on the temples (p = 0.0009). On the other hand, the ear position showed the highest subjective discomfort rating on the posterior edge of the ear, and, as opposed to the nose, the subjective discomfort ratings for the posterior edge of the ear tended to increase as the battery and circuit board moved backward (p = 0.0093). The highest nose load, 0.34 N, was found on the front position, and the load on the nose was decreased significantly as the location of the battery and circuit board moved backward (p < 0.001). Also, the nose loads had a strong correlation with the discomfort ratings on the nose (Radj 2 = 99.1%), but no strong correlation was found with the subjective discomfort ratings on the posterior edge of the ear (Radj 2 = 19.6%). Consequently, the middle position was recommended as the optimal location of the battery and circuit board on the temples of the SG type 3D glasses by considering the above results.